Development Strategy for Waisia ​​Waterfall Tourism Object in Rumahkay Village, West Seram Regency - Pattipelohy, Wendy; Tetelepta, Edward Gland; Lasaiba, Mohammad Amin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
As one of the tourist destinations, Maluku Province certainly also has several exciting waterfall tours, including Waisia ​​Waterfall. Waisia ​​Waterfall is one of the natural tourist attractions in Rumahkay Village. Waisia ​​Waterfall has excellent water and clean air. The problem in this study is how to develop the Waisia ​​waterfall tourist attraction in Rumahkay Village, West Seram Regency. This study aims to determine the strategy for creating the Waisia ​​Waterfall Tourist Attraction. This type of research is descriptive research, Which is a method widely used in research that aims to explain an event.